Handwashing knowledge and practices among caregivers of pre-school children in underprivileged areas of Nelson Mandela Bay - Steenkamp, L; Williams, M; Ronaasen, J; Feeley, A; Truter, I; Melariri, P (The South African journal of clinical nutrition, 2022)
Objectives: To explore and describe caregivers' handwashing knowledge and practices in the context of underprivileged urban communities. Design: A qualitative descriptive and exploratory study was conducted during August and September 2017, through five focus-group discussions, with caregivers of children younger than five years attending ECD centres. Setting: Early childhood development (ECD) centres in various underprivileged communities in Ibhayi and Motherwell, Nelson Mandela Bay. Subjects: Thirty-five adults, aged between 24 and 60 years, functioning as primary or secondary caregivers to 105 children, participated. Results: Three themes emerged, of which the first entailed the knowledge of handwashing and compliance with water, sanitation and hygiene (WASH) recommendations. Practical challenges that may prevent compliance with recommendations were highlighted. Handwashing as a social norm emerged as the second theme, and reflection on strategies at primary health care level to increase awareness regarding handwashing in communities was the third theme. Conclusion and recommendations: Current handwashing counselling at primary health care sites may not be perceived as relevant in underprivileged communities. However, with adequate support ECD practitioners have influence to change the handwashing behaviour and knowledge of pre-school children and families. Furthermore, communication and dissemination of handwashing messages should be clear, practical and relevant to address inappropriateness of current poster images and should include suggestions on what to do when experiencing infrastructure challenges and in times of water restrictions. Health-promotion strategies should focus on optimising handwashing practices while caring for pre-school children.